2010
DOI: 10.1364/oe.18.012436
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectra of atmospheric aerosol particles measured using one or two excitation wavelengths: Comparison of classification schemes employing different emission and scattering results

Abstract: An improved Dual-wavelength-excitation Particle Fluorescence Spectrometer (DPFS) has been reported. It measures two fluorescence spectra excited sequentially by lasers at 263 nm and 351 nm, from single atmospheric aerosol particles in the 1-10 mum diameter size range. Here we investigate the different levels of discrimination capability obtained when different numbers of excitation and fluorescence-emission wavelengths are used for analysis. We a) use the DPFS to measure fluorescence spectra of Bacillus subtil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 45 publications
3
53
0
1
Order By: Relevance
“…As judged by WIBS, the multi-channel fluorescence response observed from the seven Penicillium species aerosolized here are in general agreement with those of the Penicillium notatum by Toprak and Schnaiter (2013); they reported fluorescence emissions from P. notatum commensurate with those observed here (dominance of type A, with ascendance of type C), where these aerosolized microbes were mixed with ammonium sulfate aerosol in smallchamber studies. Pan et al (2010) also reported fluorescence (type B) associated with aerosolized B. subtilis spores similar to that reported here. The spectral distributions of B. subtilis spores reported here, and by Pan et al (2010), suggest that these aerosolized spores had markedly different fluorescence than that observed from vegetative bacterial cells with nearly the same EOD.…”
Section: Composite Optical Recognition Patterns Of Bioaerosol Classessupporting
confidence: 86%
See 1 more Smart Citation
“…As judged by WIBS, the multi-channel fluorescence response observed from the seven Penicillium species aerosolized here are in general agreement with those of the Penicillium notatum by Toprak and Schnaiter (2013); they reported fluorescence emissions from P. notatum commensurate with those observed here (dominance of type A, with ascendance of type C), where these aerosolized microbes were mixed with ammonium sulfate aerosol in smallchamber studies. Pan et al (2010) also reported fluorescence (type B) associated with aerosolized B. subtilis spores similar to that reported here. The spectral distributions of B. subtilis spores reported here, and by Pan et al (2010), suggest that these aerosolized spores had markedly different fluorescence than that observed from vegetative bacterial cells with nearly the same EOD.…”
Section: Composite Optical Recognition Patterns Of Bioaerosol Classessupporting
confidence: 86%
“…While many PBAPs fluoresce, interpreting UV-LIF measurements for bioaerosol characterization presents significant interpretive challenges, some of which have been successfully addressed using cluster analyses (Pinnick et al, 2013;Gabey et al, 2013;Crawford et al, 2015;Pan et al, 2015). In addition to classic Bayesian clustering approaches, referential methods can also be applied to analyze fluorescence distributions with selected optical properties, which may in turn be leveraged for environmental comparison(s).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a number of real-time and commercial instruments including the Ultraviolet Aerodynamic Particle Sizer (UV-APS; TSI Inc., Shoreview, MN, USA) and the Waveband Integrated Bioaerosol Sensor (WIBS; Droplet Measurement Technologies, Longmont, CO, USA) are being commonly used in bioaerosol research communities (e.g., Agranovski et al, 2003;Bhangar et al, 2014;Brosseau et al, 2000;Foot et al, 2008;Huffman et al, 2010;Perring et al, 2015;Stanley et al, 2011;Toprak and Schnaiter, 2013). The main principle common to these techniques is the detection of intrinsic fluorescence from fluorophores such as amino acids, coenzymes, vitamins, and pigments that ubiquitously occur in aerosols of biological origin (e.g., Hill et al, 2009;Pan et al, 2010;Pöhlker et al, 2012Pöhlker et al, , 2013. These PBAP represent a diverse and dynamic subset of airborne particles, consisting of whole organisms like bacteria, viruses, archaea, algae, fungi, and related reproductive units (e.g., pollen, bacterial and fungal spores), as well as decaying biomass and fragments from plants or insects (e.g., Deepak and Vali, 1991;Després et al, 2012;Jaenicke, 2005;Madelin, 1994;Pöschl, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these instruments measure single particle elastic scattering, and/or single particle fluorescence, and/or laser-or spark-induced breakdown spectroscopy (LIBS/SIBS) and some are commercially available [3]. Laser induced fluorescence (LIF), especially dual-wavelength UV-LIF has been demonstrated for near-real time detection and partial classification of bioaerosols particles [4][5][6][7][8][9]. The technique was shown to be capable of differentiating pollens from various plant species [9,10].…”
Section: Introductionmentioning
confidence: 99%